Integration of Resonant Coil for Wireless Power Transfer and Implantable Antenna for Signal Transfer - Dong-Wook Seo; Jae-Ho Lee; Hyungsoo Lee (International Journal of Antennas and Propagation)
We propose the integration of the resonant coil for wireless power transfer (WPT) and the implantable antenna for physiological signal transfer. The integration allows for a compact biomedical implantable system such as electrocardiogram (ECG) recorder and pacemaker. While the resonant coils resonate at the frequency of 13.56 MHz for the WPT, the implantable antenna works in the medical implant communications service (MICS) band of 402–405 MHz for wireless communications. They share the narrow substrate area of a bar-type shape; the coil has the current path on the outer part of the substrate and the meandered planar inverted-F antenna (PIFA) occupies the inside of the coil. To verify the potentials of the proposed structure, a prototype is fabricated and tested in vitro. The power transfer efficiency (PTE) of about 20% is obtained at a distance of 15 mm and the antenna gain of roughly −40 dBi is achieved.